PEMILIHAN UMUM MERUPAKAN PERWUJUDAN PELAKSANAAN DEMOKRASI BERDASARKAN UUD NEGARA REPUBLIK INDONESIA TAHUN 1945 - Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The constitutional system of the Republic of Indonesia is a democratic system, so the highest sovereignty is in the hands of the people, so that the people have the power to determine the election of leaders in the Republic of Indonesia. In 2024, the Government of the Republic of Indonesia has a very important agenda, namely holding General Elections for the President and Vice President. At this time, activities have begun before the general election, including political parties that have registered themselves to take part in the general election later. For this reason, it is necessary to have an understanding of the community about the importance of implementing this general election as a form of embodiment of the implementation of democracy in the administration of the state administration of the Republic of Indonesia. Therefore, it is our obligation, as academics, to carry out and assist the government so that the public will understand the implementation of democracy and carry out general elections with pleasure. For this reason, it is necessary to take steps to provide understanding by providing legal counseling to the community. Considering that the general election is held by voting from the people to choose the presidential and vice presidential candidates promoted by political parties, it is hoped that the citizens will cast their votes in this general election as well as possible. Considering that the right to vote is a human right that must be realized in accordance with the ideals of the Indonesian nation, as referred to in the Pancasila and the 1945 Constitution. For residents of the patients participating in the Prolanis Program at the Pratama Clinic